Functional regioregular (poly)urethanes from soft nucleophiles and cyclic iminocarbonates. Issue 48 (22nd November 2022) - Grignard, Bruno; Mampuys, Pieter; Escudero, Julien; Masullo, Dario; Lemière, Filip; Maes, Bert U. W.; Detrembleur, Christophe
Abstract : A method with a broad functional group tolerance is reported to produce in an atom economical fashion functional (poly)urethanes from soft (di)nucleophiles and (di)cyclic iminocarbonates, viewed as a masked version of isocyanates. Abstract : The catalyst-free synthesis of urethanes from cyclic iminocarbonates, used as masked isocyanates, and soft nucleophiles ( i.e. carboxylic acids and thiols) has been studied. Remarkably, the ring-opening reaction was fully site-selective ( i.e. methylene). The disclosed method showed high functional group tolerance towards carboxylic acids bearing alkyl-, alkenyl-, ketone-, pyrone- and hydroxyl groups. This methodology was further applied for the construction of regioregular functional polyurethanes by step-growth copolymerization of cyclic bisiminocarbonates and dicarboxylic acids or dithiols. M w up to 34 000 g mol −1 was obtained in a fully atom-economical manner using an equimolar amount of both monomers.